The Place and Effect of Animals in Families - Doré, Antoine; Michalon, Jérôme; Líbano Monteiro, Teresa (Enfances, Familles, Générations, 2019)
Research Framework : The general challenge and originality of this thematic issue of the journal Enfances Familles Générations consists in jointly exploring two major social transformations brought about by the integration of animals into families : the first transformation being in human families and the second in human-animal relationships. Objectives : The purpose of this introduction to the thematic issue "The Place and Impact of Animals in Families" is to present the current state of knowledge on the subject, by characterizing the approaches taken and identifying blind spots and how to address them. Methodology : The article is based on a review of the literature and an analysis of approximately 100 English- and French-language publications in the social sciences and humanities that focus on the place and effect of animals in families. Results : The first part of the article is devoted to an analytical presentation of the literature. Three principal methods of integrating animals into families can be identified in the works studied : integration, assimilation and substitution. In addition, two types of approaches have been favoured to date on how to understand the family in its relationship with animals : "fixist" and flexible. The second part of the article develops a critical analysis of this research. We show that, taken as a whole, these studies generate a naturalization effect of the very specific zoological, sociological and spatio-temporal realities studied. We show that this naturalization is linked to the ill-considered use of certain semantic categories ("companion animal," "family pet" or simply "pet") . It is also linked to particular systems for the production of sociological knowledge on the place of animals in families (based in part on data provided by key players in the pet industry, or created on a pointedly moral foundation). Conclusions : The article underlines the need to develop and implement a genuine sociology of family/animal relationships that, on the one hand, more candidly assumes the implicit biases that have guided research to date (a clear positioning in relation to the three methods of integrating animals into families), and on the other hand seeks to denaturalize the categories it uses while questioning the knowledge systems within which it is embedded. Contribution : Beyond a critical and problematized interpretation of the literature, this article outlines several lines of research that aim to complete and rebalance the particular image that the current literature on the dynamics of integrating animals into the family provides. Five lines are identified : (1) the symbolic construction of the integration of animals into the family (artistic and media representations, construction of categories) ; (2) the physical conditions of this integration (role of technical objects, markets) ; (3) the role of animals in the construction of the identity and socialization of families ; (4) the uses of learned and secular discourses on animal families to define and legitimize a model of human families ; (5) a sociological redefinition of the family, taking into account the different types of animal integration.